First person - Michelle Stewart (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Michelle Stewart is first author on 'Loss of Frrs1l disrupts synaptic AMPA receptor function, and results in neurodevelopmental, motor, cognitive and electrographical abnormalities', published in DMM. Michelle is a scientific manager in the lab of Sara Wells at MRC Harwell Institute, Oxfordshire, UK, investigating neurobehavioural genetics, behaviour and ageing in mice.